2021
DOI: 10.1038/s41598-021-86456-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of iron mine tailing as fillers to polyethylene

Abstract: The iron mine tailings accumulation in dams is an environmental and economic problem. The composite based on high-density polyethylene/iron mine tailing production for the application of wood plastic and some items of domestic plastic industry can be a good alternative to reduce the rejects in the environment. This work presents the influence of the processing methodology in the mechanical, thermal and morphological properties of composites based on the high-density polyethylene/iron mine tailing. Four methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In this case, largescale harmless utilization of IOTs has attracted much attention. Currently, IOTs are mainly used for IOTs recleaning (Wang et al, 2018;Zhai et al, 2020) and mine filling (Onitiri and Akinlabi, 2017;Qiu et al, 2017;Coura et al, 2021), or used as the building material (Menders et al, 2019;Li et al, 2020;Zhang et al, 2022) and soil conditioner (Santana et al, 2020;Castro e Silva et al, 2021;Cui et al, 2021). IOTs are rich in SiO 2 and Al 2 O 3 whose chemical composition is similar to that of cement (Han et al, 2017) and the physical properties are similar to those of natural sands (Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this case, largescale harmless utilization of IOTs has attracted much attention. Currently, IOTs are mainly used for IOTs recleaning (Wang et al, 2018;Zhai et al, 2020) and mine filling (Onitiri and Akinlabi, 2017;Qiu et al, 2017;Coura et al, 2021), or used as the building material (Menders et al, 2019;Li et al, 2020;Zhang et al, 2022) and soil conditioner (Santana et al, 2020;Castro e Silva et al, 2021;Cui et al, 2021). IOTs are rich in SiO 2 and Al 2 O 3 whose chemical composition is similar to that of cement (Han et al, 2017) and the physical properties are similar to those of natural sands (Huang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among the distinguishing characteristics promoting the use of HDPE are cheap cost, an easy processing procedure, and a higher level of ductility [9]. Polypropylene (PP), High-density polyethylene (HDPE) and low-density polyethylene (LDPE) are examples of some commodity polymers that are often used in packing films, mulching films and other similar applications [10][11][12][13][14][15][16]. Moreover, HDPE is a commodity plastic that is extremely valuable because to its strong chemical resistance with the inert C-C and C-H bonds, good electrical insulation, environmental resilience, and ease of moulding properties.…”
Section: Introductionmentioning
confidence: 99%
“…Martinez‐Lopez et al 16 added waste polymer particles obtained from polyethylene terephthalate bottles, polycarbonate, or tire rubber particles to unsaturated polyester resin in order to produce polymer mortars. Besides, Coura et al 17 prepared high‐density polyethylene composites using iron mine tailing as fillers. The authors showed that this waste‐based filler improve the mechanical properties and the thermal stability of HDPE but it also acts as flame‐retardant.…”
Section: Introductionmentioning
confidence: 99%